Inhalable, Spray-Dried Terbinafine Microparticles for Management of Pulmonary Fungal Infections: Optimization of the Excipient Composition and Selection of an Inhalation Device - Khaled Almansour; Iman M. Alfagih; Alhassan H. Aodah; Fawaz Alheibshy; Raisuddin Ali; Turki Al Hagbani; Mustafa M.A. Elsayed (MDPI AG, 2021)
Terbinafine is a broad-spectrum antifungal agent with therapeutic potential against pulmonary aspergillosis. The main aim of the current study was to investigate the potential of l-leucine, alone and in combination with mannitol, to improve the performance of spray-dried terbinafine microparticles for inhalation. The study also aimed to investigate the potential of the low resistance Cyclohaler® and the high resistance Handihaler® as inhalation devices for spray-dried microparticles. To this end, eight powder inhalation formulations of terbinafine were prepared by nano spray drying via a factorial experimental design. The formulations were evaluated in vitro for their potential to deliver the antifungal drug to the lungs using the Cyclohaler® and the Handihaler®. Leucine was superior as an excipient to mannitol and to mixtures of leucine and mannitol. Using leucine as an excipient resulted in formulations with fine particle fractions of up to 60.84 ± 0.67% w/w and particle mass median aerodynamic diameters of down to 1.90 ± 0.20 μm, whereas using mannitol as an excipient resulted in formulations with fine particle fractions of up to 18.75 ± 3.46% w/w and particle mass median aerodynamic diameters of down to 6.79 ± 0.82 μm. When leucine was used as an excipient, using 50% w/w rather than 25% w/w ethanol in water as a spray solvent enhanced the dispersibility of the particles, with a mean absolute increase in the formulation fine particle fraction of 9.57% w/w (95% confidence interval = 6.40-12.73% w/w). This was potentially underlain by enrichment of the particle surfaces with leucine. The Cyclohaler® outperformed the Handihaler® as an inhalation device for the developed formulations, with a mean absolute increase in the fine particle fraction of 9.17% w/w (95% confidence interval = 8.17-10.16% w/w).